BRET Biosensor Analysis of Receptor Tyrosine Kinase Functionality - Siddiqui, Sana; Cong, Wei-na; Daimon, Caitlin M.; Martin, Bronwen; Maudsley, Stuart (Frontiers in Endocrinology, 2013)
Bioluminescence resonance energy transfer (BRET) is an improved version of earlier resonance energy transfer technologies used for the analysis of biomolecular protein interaction. BRET analysis can be applied to many transmembrane receptor classes, however the majority of the early published literature on BRET has focused on G protein-coupled receptor (GPCR) research. In contrast, there is limited scientific literature using BRET to investigate receptor tyrosine kinase (RTK) activity. This limited investigation is surprising as RTKs often employ dimerization as a key factor in their activation, as well as being important therapeutic targets in medicine, especially in the cases of cancer, diabetes, neurodegenerative and respiratory conditions. In this review, we consider an array of studies pertinent to RTKs and other non-GPCR receptor protein-protein signaling interactions; more specifically we discuss receptor-protein interactions involved in the transmission of signaling communication. We have provided an overview of functional BRET studies associated with the receptor tyrosine kinase (RTK) super family involving: neurotrophic receptors (e.g. tropomyosin-related kinase (Trk) and p75 neurotrophin receptor (p75NTR)); insulinotropic receptors (e.g. insulin receptor (IR) and insulin-like growth factor receptor (IGFR)) and growth factor receptors (e.g. ErbB receptors including the EGFR, the fibroblast growth factor receptor (FGFR), the vascular endothelial growth factor receptor (VEGFR) and the c-kit and platelet-derived growth factor receptor (PDGFR)). In addition, we review BRET-mediated studies of other tyrosine kinase-associated receptors including cytokine receptors, i.e. leptin receptor (OB-R) and the growth hormone receptor (GHR). It is clear even from the relatively sparse experimental RTK BRET evidence that there is tremendous potential for this technological application for the functional investigation of RTK biology.